(untitled) (International Journal of Management (IJM), 2020)
The paper highlights the extent of awareness on the academic social media tools among the medical faculties through a survey conducted with 196 respondents from four medical colleges in Puducherry. The findings reveal that social media tools are widely acknowledged among faculties, with platforms like Instagram, Facebook, and YouTube achieving complete awareness. However, discrepancies in the usage of specific tools were noted between genders, with female faculties generally showing higher engagement. The study also highlights the positive impacts of social media on research collaboration and dissemination, while also identifying challenges such as privacy concerns and data security. However, the respondents should be motivated to make use of these tools for academic purposes through which the recognition of the institutions and their stakeholders in a better place with more visibility.